2020
DOI: 10.1093/cid/ciaa654
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Transmission During the Coronavirus Disease 2019 Pandemic and Implications for Public Health Strategies

Abstract: SARS-CoV-2 spread rapidly within months despite global public health strategies to curb transmission by testing symptomatic patients and encouraging social distancing. Here, we summarize rapidly emerging evidence highlighting transmission by asymptomatic and pre-symptomatic individuals. Viral load of asymptomatic carriers is comparable to symptomatic patients, viral shedding is highest before symptom onset suggesting high transmissibility before symptoms. Within universally tested subgroups, surprisingly high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
188
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(196 citation statements)
references
References 34 publications
5
188
0
3
Order By: Relevance
“…Irrespective of the frequency of asymptomatic carriers, they are considered to be important for the transmission of the disease [47]. Various studies reported SARS-CoV-2 infections, originating from asymptomatic carriers during close contacts such as household contacts or residents of a long-term care skilled nursing facility [43,[48][49][50][51][52]. Importantly, several studies have reported that viral RNA loads in pre-symptomatic, asymptomatic and symptomatic patients do not differ significantly [53][54][55].…”
Section: Epidemiological Relevance Of Asymptomatic Sars-cov-2 Casesmentioning
confidence: 99%
“…Irrespective of the frequency of asymptomatic carriers, they are considered to be important for the transmission of the disease [47]. Various studies reported SARS-CoV-2 infections, originating from asymptomatic carriers during close contacts such as household contacts or residents of a long-term care skilled nursing facility [43,[48][49][50][51][52]. Importantly, several studies have reported that viral RNA loads in pre-symptomatic, asymptomatic and symptomatic patients do not differ significantly [53][54][55].…”
Section: Epidemiological Relevance Of Asymptomatic Sars-cov-2 Casesmentioning
confidence: 99%
“…This underlines the need for a change of approach from symptom-based screening, especially among staff at healthcare facilities. If no routine screening is done among HCW and support staff, we may fail to detect infectious cases leading to disastrous results [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Limited by the retrospective nature of this study, it is not known whether these markers for in ammation and injuries increased around the time when severe symptoms presented. In addition, there seemed to be a mechanism for SARS-CoV-2 to escape the immune surveillance in certain patients as evidenced by the high prevalence of asymptomatic SARS-CoV-2 infected patients [21]. Therefore, another explanation is that in ammation and injuries were minimized because of immune evasion during the early disease course of critical COVID-19.…”
Section: Discussionmentioning
confidence: 99%